Improvement of irradiation-induced fibroblast damage by α2-macroglobulin through alleviating mitochondrial dysfunction - Chaoji Huangfu; Nan Tang; Xiaokun Yang; Zhanwei Gong; Junzheng Li; Junting Jia; Jingang Zhang; Yan Huang; Yuyuan Ma (Taylor & Francis Group, 2022)
Context α2-Macroglobulin (α2-M) is believed to be a potential anti-irradiation agent, but related mechanisms remains unclear.Objective We investigated the irradiation protective effect of α2-M.Materials and methods A total of 10 Gy dose of irradiation was used to damage human skin fibroblasts. The influence of α2-M (100 µg/mL) on the proliferation, migration, invasion and apoptosis of fibroblasts was observed using Cell Counting Kit-8 (CCK8), wound healing, transwell, and flow cytometry. Malondialdehyde, superoxide dismutase and catalase was measured using related ELISA kits. The levels of mitochondrial membrane potential and calcium were detected using flow cytometry. The expression of transient receptor potential melastatin 2 (TRPM2) was investigated through western blotting and immunofluorescence staining.Results High purity of α2-M was isolated from Cohn fraction IV. α2-M significantly increased cell proliferation, migration, invasion, but suppressed cell apoptosis after irradiation. The promotion of cell proliferation, migration and invasion by α2-M exceeded over 50% compared group irradiation. The increased cell ratio in the S phase and decreased cell ratio in the G2 phase induced by irradiation were remarkably reversed by α2-M. α2-M markedly suppressed the increased oxidative stress level caused by irradiation. The mitochondrial damage induced by irradiation was improved by α2-M through inhibiting mitochondrial membrane potential loss, calcium and TRPM2 expression.Discussion and conclusions α2-M significantly promoted the decreased fibroblast viability and improved the mitochondria dysfunction caused by irradiation. α2-M might present anti-radiation effect through alleviating mitochondrial dysfunction caused by irradiation. This study could provide a novel understanding about the improvement of α2-M on irradiation-induced injury.